MENGGALI DIALEKTIKA MAKNA ASBABUN NUZUL DALAM TEKS DAN REALITAS SOSIAL HISTORIS - Halimatul Udhmah, Helmi (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
This article discusses the importance of understanding the concept of asbabun nuzul in the science of interpretation, especially in relation to understanding the text of the Qur'an in a socio-historical context. The purpose of this study is to explore two main perspectives on asbabun nuzul, namely micro and macro, and how these two approaches affect our understanding of the revelation of the Qur'an. This study uses a qualitative method with a literature study and analysis of interpretations of classical and contemporary texts, as well as hadith narrations that explain the reasons for the revelation of verses. The results of the study indicate that asbabun nuzul has an important role in interpreting the verses of the Qur'an, especially in providing relevant legal and socio-cultural contexts. This study also highlights the differences in views between salaf and khalaf scholars regarding the importance of asbabun nuzul in understanding the Qur'an. Thus, understanding asbabun nuzul can enrich interpretation and help interpret verses by considering the social situation and conditions of the era when the revelation was revealed